2015
DOI: 10.1039/c5ra07428b
|View full text |Cite
|
Sign up to set email alerts
|

A rheological study on non-rubber component networks in natural rubber

Abstract: Non-rubber components, mainly indicating phospholipid and protein, were separately removed from natural rubber to individually study their effect on structure and properties of the rubber. Fourier Transform Infrared Spectroscopy (FTIR) and 1 H nuclear magnetic resonance ( 1 H NMR) were applied to characterize the chemical structure and the non-rubber component residual. Rheology study and stress relaxation measurement were adopted to study the role non-rubbers played in natural networks. Rheological study of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The loss phase angle δ versus the absolute value of the complex modulus | G *| is plotted in Figure (C), known as Van Gurp curves . It is shown that at the same phase angle, the trend of | G *| is consistent with that of complex viscosity, meaning that the length of molecular chains of coupling agents can influence the interaction between treated mica and matrix.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The loss phase angle δ versus the absolute value of the complex modulus | G *| is plotted in Figure (C), known as Van Gurp curves . It is shown that at the same phase angle, the trend of | G *| is consistent with that of complex viscosity, meaning that the length of molecular chains of coupling agents can influence the interaction between treated mica and matrix.…”
Section: Resultsmentioning
confidence: 85%
“…The G ′/ G ′′ curve is often used to illustrate the liquid‐like and solid‐like behavior of polymer composites . It is found that G ′/ G ′′ of samples all exceeds 1, meaning that there is no rheological transition from liquid‐like behavior to solid‐like behavior for these samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is clearly seen that ADS samples from the three H brasiliensis genotypes showed the highest peak A. This might be due to large networks in ADS enabling high SIC at low temperature . Furthermore, it is noteworthy that the peak A disappeared for the LPNR and AENR samples from all H brasiliensis genotypes.…”
Section: Resultsmentioning
confidence: 88%
“…This might be due to large networks in ADS enabling high SIC at low temperature. 52 Furthermore, it is noteworthy that the peak A disappeared for the LPNR and AENR samples from all H brasiliensis genotypes. This confirms that the spontaneous SIC in NR indicated by peak A in the relaxation spectra was associated with the total content of proteins and lipids together with macrogels.…”
Section: Temperature Scanning Stress Relaxationmentioning
confidence: 93%
“…It can be confirmed that the more relaxation units in NR-24 h are obviously confined by the network with abundant non-rubber components. Furthermore, the Maxwell model is used to understand the stress relaxation curves [51][52][53].…”
Section: Molecular Network Of Nr Cnr-1 and Cnr-2 Before And After Acc...mentioning
confidence: 99%